Risk factors and incidence rates of COVID-19 breakthrough infections in vaccinated people with vaccine booster in general medicine, Toledo (Spain), for the period December 2021 to February 2022 - Jose Luis Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Background: The effectiveness of vaccines against COVID-19 has been demonstrated, but because new variants appear and immunity fades over time, continuous monitoring is necessary. Objectives: To determine incidence rates (IR) and risk factors of COVID-19 breakthrough infections in vaccinated people with vaccine booster (VB). Methodology: An observational, longitudinal, and prospective study of patients with COVID-19 breakthrough infections in vaccinated people with VB in a general practice setting in Toledo, Spain, for the period December 2021 to February 2022, during the wave of infections by omicron variant. Results: Forty-six cases of COVID-19 breakthrough infections with booster shot were included. The IR was 3.1 cases per 100 people with booster. The IR was higher in < 45 years (4.7%) vs. > 65 years (4.2%), and in women (3.6%) vs. man (2.6%). The only statistically significant risk/prevention factors were the presence of diseases of the skin [RR = 2.74 (95% CI: 1.3, 5.79)], Genitourinary chronic diseases [RR = 1.87 (95% CI: 1.19, 2.95)], complex family [RR = 0.22 (CI 95%: 0.58, 0.08)] and chronic diseases of the mental group [RR = 0.4 (95% CI: 0.82, 0.2)]. Conclusion: The IR of COVID-19 breakthrough infections with a booster shot, at the peak of omicron infections (December 2021-February 2022), in the general medicine clinic, Toledo, Spain, was high, suggesting modest VB protection effectiveness against symptomatic infection. Statistically significant risk and protective factors show mixed results; so, it is hypothesized that they are related to other main variables such as gender and age, and/or with risk/preventive behaviors. However, the small numbers of COVID-19 breakthrough infections with booster shots prevent definitive conclusions.